Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Toward Facilities Management Practice Within Different Environment M. Ali Modu, Maimunah Sapri & Zafirah Abd Muin Influence of Sustainable Construction Practices Awareness Level on Extent of Usage in Abuja-Nigeria R. Jimoh, L. Oyewobi, E. Ogunbode, R. Isa, A. Bilau & A. Yusuf The Other Sensory Approach on Exploring Urban Heritage Landscape. Case Study: Chinese Quarter of Semarang Auliya M. Alqadrie & Widjaja Martokusumo SWOT Analysis of Formation of Modern Irrigation Management Unit in DI Kromong (Kromong Irrigation Area), Kabupaten Mojokerto Rochmad Afandi, Nadjadji Anwar & Theresia Sri Sidharti The Physical Integration of Smart Transportation Characteristics of Suroboyo Bus and the Feeder Cindy Nur Aziza Rahman, Eko Budi Santoso & Siti Nurlaela